Influential Factors in the Success of the Merdeka Belajar Kampus Merdeka (MBKM) Program Implementation: A Case Study Among Students - Nur Rahmawati, Ajeng Intan; Susanti, Romia Hari; Permatasari, Devi; Ariffudin, Imam (Jurnal inspirasi pendidikan (Online), 2024)
The implementation of the Merdeka Belajar Kampus Merdeka (MBKM) Program has a positive impact on the competencies of Guidance and Counseling students in the field as practitioners. This study aims to analyze the factors influencing the successful implementation of the MBKM program among students. A qualitative method was employed, utilizing a case study design with a program review option. Six students were selected as research subjects using the random sampling technique. The instruments used in this study included interview sheets, evaluation sheets, and documentation forms. Thematic analysis was utilized to examine the collected data. The analysis results indicate that three general themes contribute positively to the competencies of counselors: supporting system, experience learning, and satisfaction. The supporting system includes institutional support, mentorship, and student resources. Experience learning refers to the hands-on, practical experiences that students gain in the field, which enhance their understanding and skills. Satisfaction encompasses the students' overall contentment with the program and their perceived value of the learning experiences. Based on these results, this study can serve as a reference for future evaluations and improvements in implementing the MBKM program. These findings underscore the importance of a well-supported learning environment, practical experience, and student satisfaction in developing the competencies of Guidance and Counseling students in the field.